Constitutionalism and fundamental rights in Latin America: Three historical models - Ramos Núñez, Carlos (2019)
Human rights in Latin America have historically manifested themselves through three conceptions. The first lies mainly in natural law individualism; in the second, the axis moves from the individual to other centers of regulatory imputation such as family, labor unions, work, education, health, opening a social perspective of fundamental rights. Finally, a naturalist vision is imposed, one that transcends the individual and the community and rests on the landscape, the land and the water.